FASILITATOR DALAM KOMUNIKASI PEMBERDAYAAN MASYARAKAT - Jumrana Jurmrana (Profetik: Jurnal Komunikasi, 2015)
This study attempted to describe the methods of communication used facilitators in community development and its role as an agent of development. The method used was a combination method. Data were collected through a survey of the community, and interviews in the facilitator. Research has been conducted in three villages in Kendari are considered successful in community development activities This method of communication conducted in interactions between facilitators and communities in community development activities have contributed to the success of the program despite the rare interactions.Communication through the individuals who play a role in the more intensive group, it is proven effective to disseminate information to members and other community groups through informal communication. Nevertheless, there is a gap between the role played by facilitators and the role of the facilitators is expected by society. People not only want facilitators becomes consultant or mediator, but they expect facilitators can help them solve various problems and facilitate their program proposals to the government. In fact, at this stage, the community has been quite independent in planning and managing community development activities.